Quantitative feedback theory based robust speed control of vector controlled induction motor - Krishnankutty, Jisha Lakshmi; Thomas, Arekkadan Antony Powly; Srivastava, Suresh (Institute of Advanced Engineering and Science, 2023)
In this research paper a method for the robust speed control of Indirect Field orient controlled induction motor (IM) is proposed. The quantitative feedback theory (QFT) in implemented to design the controller in order to achieve the desired performance for the closed loop system in the presence of uncertainties and parameter variations. In this research work the QFT based controller is designed for the simplified model of IM. The worst case of uncertainties and all possible parameter variations are taken into consideration. The IM with the controller developed is simulated using the MATLAB/Simulink and the results are analyzed and compared with the conventional proportional integral derivative (PID) controller. The time domain and frequency domain analysis of both controllers were conducted and compared. A study on the nature of electromagnetic torque and control signal is also included to justify the effectiveness of proposed controller. The simulation results verify the superior performance of the proposed robust control method compared to PID controller.